Adhesive film, acrylic adhesive composition and flexible device
An adhesive film with an acrylic adhesive layer addressing the poor flexing characteristics of conventional films by providing high flexibility, strong adhesion, and cohesive power, ensuring durability in flexible devices and semiconductor substrates.
Patent Information
- Application Number
- JP2023172080
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
AI Technical Summary
Conventional adhesive films used in flexible devices and semiconductor substrates often have poor flexing characteristics, leading to reduced recovery after bending and potential damage to the semiconductor device due to repeated bending.
The development of an adhesive film with an acrylic adhesive layer that has a low storage elastic modulus at low temperatures, high shear retention rate, and high creep value, ensuring both high flexibility and strong adhesion to the adherend.
The adhesive film achieves high flexibility, sufficient adhesion, and high cohesive power, effectively withstanding stress during bending and maintaining performance in low-temperature environments.
Smart Images

Figure 2025062805000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive film, an acrylic adhesive composition, and a flexible device. [Background technology]
[0002] Adhesive films are used for reinforcing members of various shapes and for protecting the surfaces.
[0003] For example, when joining an integrated circuit (IC) or a flexible printed circuit (FPC) to a substrate of a semiconductor element (e.g., a TFT substrate, etc.), thermocompression bonding is usually performed using an anisotropic conductive film (ACF). When performing such thermocompression bonding, an adhesive film may be attached to the back side of the substrate of the semiconductor element in advance to reinforce the substrate (e.g., Patent Document 1).
[0004] In addition, in a manufacturing method for so-called flexible devices such as foldable devices and rollable devices, which have been developed in recent years, a release layer and a flexible film substrate are generally formed on a support substrate such as glass, a TFT substrate is formed on the film substrate, and an organic EL layer is further formed on the TFT substrate. The support substrate is then peeled off to manufacture a flexible device, but since the flexible display layer is very thin, problems with the device occur due to handling, etc. For this reason, an adhesive film may be attached to the back side to reinforce it (for example, Patent Document 2).
[0005] Substrates of semiconductor elements and flexible devices may be repeatedly bent, and if the bending characteristics of the adhesive film attached to the substrate, etc. are poor, the recovery after bending may be poor, or in the worst case, the repeated bending may cause the film to break.
[0006] In order to provide a pressure-sensitive adhesive film with good flexibility, the pressure-sensitive adhesive contained in the pressure-sensitive adhesive film is required to have a low elastic modulus. Generally, the elastic modulus in the low temperature range is higher than that in the normal temperature range. Therefore, the pressure-sensitive adhesive film is required to have a low elastic modulus in the low temperature range.
[0007] However, conventionally, when the elastic modulus of a pressure-sensitive adhesive is reduced in the low temperature range, there are problems such as a decrease in adhesion between the pressure-sensitive adhesive and the adherend, and a decrease in the cohesive strength of the pressure-sensitive adhesive, which makes the pressure-sensitive adhesive film unable to withstand the stress when bent. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 5600039 [Patent Document 2] Patent No. 6376271 Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to provide an adhesive film including an adhesive layer composed of an acrylic adhesive, which can simultaneously exhibit high flexibility, sufficient adhesion to an adherend, and high cohesive strength of the acrylic adhesive. The object of the present invention is also to provide an acrylic adhesive composition capable of constituting an acrylic adhesive capable of simultaneously exhibiting high flexibility, sufficient adhesion to an adherend, and high cohesive strength. The object of the present invention is also to provide a flexible device including such an adhesive film. [Means for solving the problem]
[0010] [1] An adhesive film according to an embodiment of the present invention is an adhesive film including an adhesive layer composed of an acrylic adhesive, wherein the adhesive strength of the acrylic adhesive to a polyimide film at 23°C, at a peel speed of 10 mm / min and a peel angle of 180° is 700 gf / 25 mm or more, the adhesive strength of the acrylic adhesive to a polyimide film at 23°C, at a peel speed of 6000 mm / min and a peel angle of 180° is 1300 gf / 25 mm or more, and the storage modulus of the acrylic adhesive at -20°C is less than 140 kPa. [2] In the pressure-sensitive adhesive film described in [1] above, the acrylic pressure-sensitive adhesive may have a shear retention of 50% or more. [3] In the pressure-sensitive adhesive film according to the above [1] or [2], the acrylic pressure-sensitive adhesive may have a creep value of 45% or more at -20°C. [4] An acrylic pressure-sensitive adhesive composition according to an embodiment of the present invention is an acrylic pressure-sensitive adhesive composition that forms an acrylic pressure-sensitive adhesive, the acrylic pressure-sensitive adhesive composition including an acrylic polymer, an acrylic oligomer, and two or more types of crosslinking agents. [5] In the acrylic pressure-sensitive adhesive composition according to the above item [4], the two or more crosslinking agents may include an epoxy crosslinking agent. [6] In the acrylic pressure-sensitive adhesive composition described in [5] above, the two or more types of crosslinking agents may include two types of crosslinking agents: an epoxy crosslinking agent and an isocyanate crosslinking agent. [7] In the acrylic pressure-sensitive adhesive composition according to the above [5] or [6], the content of the epoxy crosslinking agent per 100 parts by weight of the acrylic polymer may be 0.05 parts by weight or more. [8] In the acrylic pressure-sensitive adhesive composition according to any one of [4] to [7] above, the content of the acrylic oligomer per 100 parts by weight of the acrylic polymer may be 5 parts by weight or more. [9] In the acrylic pressure-sensitive adhesive composition according to any one of the above items [4] to [8], the acrylic oligomer may be a carboxyl group-containing acrylic oligomer.
[10] In the acrylic pressure-sensitive adhesive composition according to any one of the above items [4] to [9], the acrylic polymer may be a hydroxyl group-containing acrylic polymer.
[11] A flexible device according to an embodiment of the present invention includes the adhesive film described in any one of [1] to [3] above. Effect of the Invention
[0011] According to the present invention, it is possible to provide an adhesive film including an adhesive layer composed of an acrylic adhesive, which can simultaneously exhibit high flexibility, sufficient adhesion to an adherend, and high cohesive strength of the acrylic adhesive. According to the present invention, it is also possible to provide an acrylic adhesive composition capable of constituting an acrylic adhesive capable of simultaneously exhibiting high flexibility, sufficient adhesion to an adherend, and high cohesive strength. According to the present invention, it is also possible to provide a flexible device including such an adhesive film. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a flexible device of the present invention, and shows one mode of use of an adhesive film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein". In this specification, the term "acid (salt)" means "acid and / or its salt". Examples of salts include alkali metal salts and alkaline earth metal salts, and specific examples include sodium salts and potassium salts.
[0014] ≪≪1. Adhesive film≫≫ The pressure-sensitive adhesive film according to the embodiment of the present invention is a pressure-sensitive adhesive film including a pressure-sensitive adhesive layer made of an acrylic pressure-sensitive adhesive.
[0015] The pressure-sensitive adhesive film according to the embodiment of the present invention may be a substrate-less film consisting of only a pressure-sensitive adhesive layer, or may be a substrate-attached film having a substrate layer and a pressure-sensitive adhesive layer. The pressure-sensitive adhesive film of the present invention may include any other appropriate layer in addition to the substrate layer and the pressure-sensitive adhesive layer, as long as the effect of the present invention is not impaired.
[0016] The substrate layer may be one layer or two or more layers, and is preferably one layer in that the effects of the present invention can be more effectively exhibited.
[0017] The pressure-sensitive adhesive layer may be one layer or two or more layers, and is preferably one layer in that the effect of the present invention can be more effectively exhibited.
[0018] The pressure-sensitive adhesive film according to the embodiment of the present invention may be provided with any suitable release liner on the surface of the pressure-sensitive adhesive layer opposite to the surface on which the base layer is provided, for protection or the like until use.
[0019] Examples of the release liner include a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is silicone-treated, and a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin resin. Examples of the plastic film as the liner substrate include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polybutylene terephthalate film, a polyurethane film, and an ethylene-vinyl acetate copolymer film.
[0020] The thickness of the release liner is preferably from 1 μm to 500 μm, more preferably from 3 μm to 450 μm, still more preferably from 5 μm to 400 μm, and particularly preferably from 10 μm to 300 μm.
[0021] The total thickness of the pressure-sensitive adhesive film according to the embodiment of the present invention is preferably 1 μm to 500 μm, more preferably 5 μm to 200 μm, even more preferably 10 μm to 150 μm, particularly preferably 20 μm to 100 μm, and most preferably 30 μm to 80 μm. When the thickness of the pressure-sensitive adhesive film according to the embodiment of the present invention is within the above range, the effects of the present invention can be more effectively exhibited.
[0022] ≪1-1. Base material layer≫ The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, further preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. When the thickness of the substrate layer is within the above range, the effects of the present invention can be more effectively exhibited.
[0023] As the material for the base layer, any appropriate material may be used as long as it does not impair the effects of the present invention. A representative example of the material for the base layer is a resin material.
[0024] Examples of resin materials for the base layer include acrylic resins such as polyimide (PI), polyether ether ketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, and cyclic olefin polymers.
[0025] <1-2. Adhesive layer> The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, even more preferably 10 μm to 100 μm, particularly preferably 10 μm to 80 μm, and most preferably 10 μm to 60 μm. When the thickness of the pressure-sensitive adhesive layer is within the above range, the effects of the present invention can be more effectively exhibited.
[0026] The adhesive layer is composed of an acrylic adhesive. More specifically, the adhesive layer is a layer of an acrylic adhesive. Any suitable forming method can be adopted as a method for forming the adhesive layer within the scope of the present invention. For example, an acrylic adhesive composition is applied to any suitable substrate, heated and dried as necessary, and cured as necessary to form an adhesive layer composed of an acrylic adhesive on the substrate. Any suitable means can be adopted as a means for such application within the scope of the present invention. For example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roll brush coater can be cited as examples of such means for application. Any suitable means can be adopted for heating and drying the acrylic adhesive composition within the scope of the present invention. For example, a means for such heating and drying can be heating to about 60°C to 180°C. The acrylic pressure-sensitive adhesive composition may be cured by any suitable means as long as the effects of the present invention are not impaired. Examples of such curing means include ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0027] <1-2-1. Acrylic adhesive> In the adhesive film according to the embodiment of the present invention, the adhesive strength of the acrylic adhesive to the polyimide film at 23°C, peel speed 10mm / min, peel angle 180° is preferably 700gf / 25mm or more, more preferably 800gf / 25mm or more, even more preferably 850gf / 25mm or more, and particularly preferably 900gf / 25mm or more. The upper limit of the adhesive strength is preferably as large as possible, but in reality, it is preferably 3000gf / 25mm or less. The adhesive strength of the acrylic adhesive to the polyimide film at 23°C, peel speed 10mm / min, peel angle 180° is higher, the higher the measured value, the higher the adhesion between the acrylic adhesive and the adherend. This is because the peel speed is slow at 10mm / min, so the cohesive force of the acrylic adhesive during measurement is small, and the adhesive strength of the acrylic adhesive to the adherend interface is largely reflected in the measured value. Therefore, in the pressure-sensitive adhesive film according to the embodiment of the present invention, if the adhesive strength of the acrylic pressure-sensitive adhesive to the polyimide film at 23° C., a peel speed of 10 mm / min, and a peel angle of 180° is within the above range, the acrylic pressure-sensitive adhesive can exhibit sufficient adhesion to the adherend. The method for measuring the adhesive strength will be described in detail later.
[0028] In the adhesive film according to the embodiment of the present invention, the adhesive strength of the acrylic adhesive to the polyimide film at 23°C, peel speed 6000mm / min, peel angle 180° is preferably 1300gf / 25mm or more, more preferably 1350gf / 25mm or more, even more preferably 1400gf / 25mm or more, particularly preferably 1450gf / 25mm or more, and most preferably 1500gf / 25mm or more. The upper limit of the adhesive strength is preferably as large as possible, but in reality, it is preferably 2500gf / 25mm or less. The adhesive strength of the acrylic adhesive to the polyimide film at 23°C, peel speed 6000mm / min, peel angle 180° is higher, the higher the measured value, the higher the cohesive strength of the acrylic adhesive. This is because the peel speed is as fast as 6000mm / min, so that the adhesion force of the acrylic adhesive to the adherend interface during measurement is reduced, and the cohesive strength of the acrylic adhesive is largely reflected in the measured value. Therefore, in the pressure-sensitive adhesive film according to the embodiment of the present invention, if the adhesive strength of the acrylic pressure-sensitive adhesive to the polyimide film at 23° C., peel speed of 6000 mm / min, and peel angle of 180° is within the above range, the acrylic pressure-sensitive adhesive can exhibit high cohesive strength. The method for measuring the adhesive strength will be described in detail later.
[0029] In the pressure-sensitive adhesive film according to the embodiment of the present invention, the storage modulus of the acrylic pressure-sensitive adhesive at -20°C is preferably less than 140 kPa, more preferably less than 135 kPa, even less than 130 kPa, particularly less than 125 kPa, and most preferably less than 120 kPa. From the viewpoint of handling and the like, the lower limit of the storage modulus is preferably 30 kPa or more in reality. In the pressure-sensitive adhesive film according to the embodiment of the present invention, if the storage modulus of the acrylic pressure-sensitive adhesive at -20°C is within the above range, the acrylic pressure-sensitive adhesive has a low modulus in the low temperature range, and therefore can exhibit high flexibility. The method for measuring the storage modulus at -20°C will be described in detail later.
[0030] In the pressure-sensitive adhesive film according to the embodiment of the present invention, the acrylic pressure-sensitive adhesive has a shear retention of preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, particularly preferably 74% or more, and most preferably 78% or more. The upper limit of the shear retention is practically 100% or less. Since the acrylic pressure-sensitive adhesive is subjected to a stress in the shear direction when bent, the higher the shear retention of the acrylic pressure-sensitive adhesive, the higher the peel resistance when bent. If the shear retention is low, the acrylic pressure-sensitive adhesive may peel off from the adherend or cohesive failure may occur in the acrylic pressure-sensitive adhesive when bent. The method for measuring the shear retention will be described in detail later.
[0031] In the pressure-sensitive adhesive film according to the embodiment of the present invention, the acrylic pressure-sensitive adhesive preferably has a creep value of 45% or more, more preferably 47% or more, even more preferably 49% or more, and particularly preferably 50% or more at -20°C. The upper limit of the creep value is usually the higher the better, but taking into consideration the balance with other pressure-sensitive adhesive properties, etc., it is preferably 200% or less. The creep value at -20°C is an index of stress relaxation properties against bending in a low-temperature environment, and the higher it is, the better the stress relaxation properties against bending in a low-temperature environment are. If the creep value at -20°C is low, the stress relaxation properties against bending in a low-temperature environment are low, and there is a risk of causing cracking or breakage of surrounding members when bending. The method for measuring the creep value at -20°C will be described in detail later.
[0032] In the adhesive film according to the embodiment of the present invention, it is more preferable that the acrylic adhesive has all three of the above-mentioned preferred ranges: (1) adhesive strength to polyimide film at 23°C, peel speed of 10 mm / min, peel angle of 180°, (2) adhesive strength to polyimide film at 23°C, peel speed of 6000 mm / min, peel angle of 180°, and (3) storage modulus at -20°C. By adjusting in this way, an adhesive film can be obtained that can simultaneously exhibit high flexibility, sufficient adhesion to the adherend, and high cohesive strength of the acrylic adhesive. As mentioned above, in the design of an adhesive that can exhibit flexibility, the elastic modulus of the adhesive in the low temperature range and the adhesion between the adhesive and the adherend and the cohesive strength of the adhesive are in a trade-off relationship. The adhesive film according to the embodiment of the present invention can satisfactorily achieve the elastic modulus of the adhesive in the low temperature range and the adhesion between the adhesive and the adherend and the cohesive strength of the adhesive, which are in a trade-off relationship in the past.
[0033] In the adhesive film according to the embodiment of the present invention, from the viewpoint of enabling the acrylic adhesive to exhibit better flexibility, it is further preferred that all three of (1), (2), and (3) above are adjusted to be within the above preferred ranges, and further that at least one selected from the group consisting of (4) shear retention and (5) creep value at -20°C above is adjusted to be within the above preferred ranges.
[0034] In the pressure-sensitive adhesive film according to the embodiment of the present invention, the acrylic pressure-sensitive adhesive is preferably formed from an acrylic pressure-sensitive adhesive composition.
[0035] An acrylic adhesive can be defined as something formed from an acrylic adhesive composition in this way. This is because an acrylic adhesive becomes an acrylic adhesive when an acrylic adhesive composition undergoes a crosslinking reaction or the like due to heating or exposure to ultraviolet light, making it impossible and practical to directly identify an acrylic adhesive by its structure ("impossible / impractical circumstances"). Therefore, the definition of "something formed from an acrylic adhesive composition" appropriately identifies an acrylic adhesive as a "product."
[0036] When the acrylic adhesive is formed from an acrylic adhesive composition, any suitable method may be adopted as the method for forming the acrylic adhesive, as long as it does not impair the effects of the present invention. Examples of the method for forming such an acrylic adhesive include a method in which the acrylic adhesive composition is applied to any suitable substrate, heated and dried as necessary, and cured as necessary to form an acrylic adhesive on the substrate. Any suitable means may be adopted as the means for such application, as long as it does not impair the effects of the present invention. Examples of such means for application include a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roll brush coater. Any suitable means may be adopted for heating and drying the acrylic adhesive composition, as long as it does not impair the effects of the present invention. Examples of such means for heating and drying include heating to about 60°C to 180°C. The acrylic pressure-sensitive adhesive composition may be cured by any suitable means as long as the effects of the present invention are not impaired. Examples of such curing means include ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0037] The pressure-sensitive adhesive film according to the embodiment of the present invention includes a pressure-sensitive adhesive layer composed of an acrylic pressure-sensitive adhesive, and the acrylic pressure-sensitive adhesive is preferably formed from an acrylic pressure-sensitive adhesive composition as described above. Any appropriate acrylic pressure-sensitive adhesive composition may be adopted as the acrylic pressure-sensitive adhesive composition as long as the effects of the present invention are not impaired. From the viewpoint of further exerting the effects of the present invention, the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention described below may be preferably adopted as the acrylic pressure-sensitive adhesive composition.
[0038] <<2. Acrylic adhesive composition>> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention is an acrylic pressure-sensitive adhesive composition that forms an acrylic pressure-sensitive adhesive.
[0039] The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains an acrylic polymer, an acrylic oligomer, and two or more crosslinking agents. The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention can effectively exhibit the effects of the present invention by containing an acrylic oligomer and two or more crosslinking agents in addition to an acrylic polymer as a base polymer. If the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention does not contain an acrylic oligomer or contains only one type of crosslinking agent, the effects of the present invention may not be exhibited.
[0040] The content of the acrylic polymer in the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention is preferably 50% by weight or more, more preferably 70% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 97% by weight or more, in order to further exert the effects of the present invention. The upper limit of the content is preferably 100% by weight or less.
[0041] In the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention, the content of the acrylic oligomer relative to 100 parts by weight of the acrylic polymer is preferably 5 parts by weight or more, more preferably 5 parts by weight or more and less than 16 parts by weight, even more preferably 6 parts by weight or more and less than 15 parts by weight, particularly preferably 7 parts by weight or more and less than 14 parts by weight, and most preferably 8 parts by weight or more and less than 13 parts by weight. If the content of the acrylic oligomer is within the above range, the effect of the present invention can be more effectively exhibited. If the content of the acrylic oligomer is too small, the effect of the present invention may not be exhibited, for example, the adhesion between the acrylic pressure-sensitive adhesive and the adherend may be reduced. If the content of the acrylic oligomer is too large, the effect of the present invention may not be exhibited, for example, the elastic modulus in the low temperature range may be high.
[0042] In the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention, the total content of the two or more crosslinking agents relative to 100 parts by weight of the acrylic polymer is preferably 0.05 parts by weight or more, more preferably 0.10 parts by weight or more and less than 3.00 parts by weight, even more preferably 0.15 parts by weight or more and less than 2.50 parts by weight, even more preferably 0.20 parts by weight or more and less than 2.00 parts by weight, even more preferably 0.25 parts by weight or more and less than 1.50 parts by weight, even more preferably 0.30 parts by weight or more and less than 1.50 parts by weight, even more preferably 0.35 parts by weight or more and less than 1.40 parts by weight, particularly preferably 0.40 parts by weight or more and less than 1.30 parts by weight, and most preferably 0.45 parts by weight or more and less than 1.20 parts by weight.
[0043] 2-1. Acrylic polymers The acrylic polymer may be of only one type, or of two or more types.
[0044] The weight average molecular weight Mw of the acrylic polymer is preferably 2.5 million or less, more preferably 2.4 million or less, even more preferably 2.3 million or less, even more preferably 2.2 million or less, and particularly preferably 2.1 million or less. The lower limit of the weight average molecular weight Mw is preferably 1 million or more. The method for measuring the weight average molecular weight Mw will be described in detail later.
[0045] The acrylic polymer is preferably a hydroxyl group-containing acrylic polymer in that the effects of the present invention can be more effectively exhibited.
[0046] The acrylic polymer is obtained by polymerizing the monomer component (M).
[0047] An acrylic polymer can be defined as something obtained by polymerizing the monomer component (M) in this way. This is because an acrylic polymer becomes an acrylic polymer through a polymerization reaction of the monomer component (M), and it is impossible and almost impractical to directly identify an acrylic polymer by its structure ("impossible / impractical circumstances") exist, so the definition of "something obtained by polymerizing the monomer component (M)" appropriately identifies an acrylic polymer as a "product."
[0048] The monomer component (M) preferably contains an alkyl (meth)acrylate. The alkyl group of the ester moiety is preferably an alkyl group having 1 to 16 carbon atoms. The alkyl group of the ester moiety here does not include an alkyl group containing a polar group such as a hydroxyl group. The alkyl (meth)acrylate may be of only one type, or of two or more types.
[0049] The content of the alkyl (meth)acrylate in the monomer component (M) is preferably 50% by weight to 99% by weight, more preferably 70% by weight to 99% by weight, even more preferably 80% by weight to 99% by weight, still more preferably 90% by weight to 99% by weight, particularly preferably 95% by weight to 99% by weight, and most preferably 97% by weight to 99% by weight, so that the effects of the present invention can be more effectively exhibited. When the content of the alkyl (meth)acrylate in the monomer component (M) is within the above range, the effects of the present invention can be more effectively exhibited.
[0050] As the alkyl (meth)acrylate, any suitable alkyl (meth)acrylate can be used as long as it does not impair the effects of the present invention. As such an alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used. CH2=C(R 1 )COOR 2 (1)
[0051] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group, and R 2 is an alkyl group having 1 to 20 carbon atoms.
[0052] R 2 is preferably an alkyl group having 1 to 16 carbon atoms, more preferably an alkyl group having 2 to 14 carbon atoms, still more preferably an alkyl group having 4 to 14 carbon atoms, and particularly preferably an alkyl group having 4 to 12 carbon atoms, in that the effects of the present invention can be more effectively exhibited.
[0053] The alkyl group is preferably a chain alkyl group, in that the effects of the present invention can be more effectively exhibited. Here, the term "chain" includes both linear and branched alkyl groups.
[0054] R 2Examples of alkyl(meth)acrylates in which is a chain alkyl group having 1 to 20 carbon atoms include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, isooctyl(meth)acrylate, ) acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0055] In terms of being able to further exert the effects of the present invention, the alkyl (meth)acrylate that can be contained in the monomer component (M) has a glass transition temperature Tg of its homopolymer (homopolymer) of preferably -10 ° C or less, more preferably -12 ° C or less, even more preferably -15 ° C or less, particularly preferably -18 ° C or less, and most preferably -20 ° C or less. The lower limit of the glass transition temperature Tg is preferably -80 ° C or more. The glass transition temperature Tg of the homopolymer (homopolymer) of the alkyl (meth)acrylate that can be contained in the monomer component (M) can affect the adhesive properties and bending properties of the acrylic polymer. By adopting an alkyl (meth)acrylate whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range as the alkyl (meth)acrylate that can be contained in the monomer component (M), the adhesive properties and bending properties of the acrylic polymer can be appropriately adjusted, and the effects of the present invention can be further exerted.
[0056] Here, as the glass transition temperature Tg of a homopolymer of an alkyl (meth)acrylate that may be contained in the monomer component (M), a value described in a publicly known document can be used, for example, the numerical value described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989). When multiple numerical values are described in the "Polymer Handbook," the conventional value is used. For an alkyl (meth)acrylate not described in the "Polymer Handbook," the catalog value of the monomer manufacturer is used. For the Tg of an alkyl (meth)acrylate homopolymer that is not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.
[0057] Representative examples of the glass transition temperature Tg of a homopolymer of an alkyl (meth)acrylate that can be contained in the monomer component (M) are as follows. 2-Ethylhexyl acrylate (2EHA): -70℃ Lauryl acrylate (LA): -23℃ n-Butyl acrylate (BA): -55℃
[0058] From the viewpoint of further exerting the effects of the present invention, the monomer component (M) preferably contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m1) whose homopolymer has a glass transition temperature Tg in the range of −80° C. to −60° C. When the monomer component (M) contains the alkyl (meth)acrylate (m1), from the viewpoint of further exerting the effects of the present invention, the content of the alkyl (meth)acrylate (m1) in the monomer component (M) is preferably 40% by weight to 99% by weight, more preferably 50% by weight to 90% by weight, even more preferably 55% by weight to 85% by weight, particularly preferably 60% by weight to 80% by weight, and most preferably 65% by weight to 75% by weight.
[0059] An example of the alkyl (meth)acrylate (m1) is 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg of its homopolymer is −70° C.).
[0060] In order to further exert the effects of the present invention, the monomer component (M) preferably contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m2) whose homopolymer has a glass transition temperature Tg in the range of −40° C. to −10° C. When the monomer component (M) contains the alkyl (meth)acrylate (m2), in order to further exert the effects of the present invention, the content of the alkyl (meth)acrylate (m2) in the monomer component (M) is preferably 1 wt % to 50 wt %, more preferably 3 wt % to 30 wt %, even more preferably 4 wt % to 20 wt %, particularly preferably 5 wt % to 15 wt %, and most preferably 6 wt % to 10 wt %.
[0061] An example of the alkyl (meth)acrylate (m2) is lauryl acrylate (LA) (the glass transition temperature Tg of its homopolymer is −23° C.).
[0062] From the viewpoint of further exerting the effects of the present invention, it is preferable that the monomer component (M) contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m3) whose homopolymer has a glass transition temperature Tg in the range of more than −60° C. and less than −40° C. When the monomer component (M) contains the alkyl (meth)acrylate (m3), from the viewpoint of further exerting the effects of the present invention, the content of the alkyl (meth)acrylate (m3) in the monomer component (M) is preferably 1 wt % to 45 wt %, more preferably 3 wt % to 40 wt %, even more preferably 5 wt % to 35 wt %, particularly preferably 10 wt % to 30 wt %, and most preferably 15 wt % to 25 wt %.
[0063] An example of the alkyl (meth)acrylate (m3) is n-butyl acrylate (BA) (the glass transition temperature Tg of its homopolymer is −55° C.).
[0064] In terms of being able to further exert the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), and even more preferably contains any of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3).
[0065] In terms of being able to further exert the effects of the present invention, typically, monomer component (M) preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and even more preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate.
[0066] The monomer component (M) preferably contains a hydroxyl group-containing monomer (m4). The hydroxyl group-containing monomer (m4) may be of one type only, or of two or more types.
[0067] In terms of being able to further exert the effects of the present invention, the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) has a glass transition temperature Tg of its homopolymer (homopolymer) of preferably -10 ° C. or less, more preferably -15 ° C. or less, even more preferably -20 ° C. or less, particularly preferably -25 ° C. or less, and most preferably -30 ° C. or less. The lower limit of the glass transition temperature Tg is preferably -80 ° C. or more. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) can affect the adhesive properties and bending properties of the acrylic polymer. By adopting a hydroxyl group-containing monomer (m4) whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range as the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M), the adhesive properties and bending properties of the acrylic polymer can be appropriately adjusted, and the effects of the present invention can be further exerted.
[0068] Here, the glass transition temperature Tg of the homopolymer of the hydroxyl group-containing monomer (m4) that may be contained in the monomer component (M) may be determined in the same manner as the glass transition temperature Tg of the homopolymer of the aforementioned alkyl (meth)acrylate.
[0069] Representative examples of the glass transition temperature Tg of the homopolymer of the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) are as follows. 2-Hydroxyethyl acrylate: -15℃ 4-Hydroxybutyl acrylate: -40℃
[0070] When the monomer component (M) contains a hydroxyl group-containing monomer (m4), in order to further exert the effects of the present invention, the content of the hydroxyl group-containing monomer (m4) in the monomer component (M) is preferably 0.01 wt % to 30 wt %, more preferably 0.05 wt % to 10 wt %, even more preferably 0.1 wt % to 5.0 wt %, particularly preferably 0.3 wt % to 3.0 wt %, and most preferably 0.5 wt % to 1.5 wt %.
[0071] Examples of the hydroxyl group-containing monomer (m4) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide.
[0072] In terms of being able to further exert the effects of the present invention, the hydroxyl group-containing monomer (m4) preferably contains a hydroxyalkyl (meth)acrylate, and more preferably contains a hydroxyalkyl (meth)acrylate in which the alkyl group moiety is a linear alkyl group having 2 to 4 carbon atoms. Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA), and in terms of being able to further exert the effects of the present invention, 4-hydroxybutyl acrylate is preferred.
[0073] In order to further exert the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4), and even more preferably contains all of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4).
[0074] In terms of being able to further exert the effects of the present invention, typically, the monomer component (M) preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4), more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4), and even more preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4).
[0075] The monomer component (M) may contain other monomers within the range that does not impair the effects of the present invention. The other monomers can be used for the purpose of, for example, adjusting the glass transition temperature (Tg) of the acrylic polymer, adjusting the adhesive performance, etc. The other monomers may be one type only, or two or more types.
[0076] Examples of the other monomers include carboxy group-containing monomers, nitrogen-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, acid anhydride group-containing monomers, vinyl esters (e.g., vinyl acetate (VAc), vinyl propionate, vinyl laurate), aromatic vinyl compounds, amide group-containing monomers, epoxy group-containing monomers, (meth)acryloylmorpholine, and vinyl ethers.
[0077] Examples of carboxy group-containing monomers include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0078] Examples of the nitrogen-containing monomer include nitrogen-containing vinyl monomers such as N-vinyl-2-pyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam; and cyano group-containing acrylic monomers such as acrylonitrile and methacrylonitrile.
[0079] As the other monomer, N-vinyl-2-pyrrolidone is preferred because it has a high effect of improving adhesive strength by improving cohesive strength.
[0080] The content of other monomers in the monomer component (M) is preferably 0% by weight to 20% by weight, more preferably 0% by weight to 10% by weight, even more preferably 0% by weight to 5% by weight, particularly preferably 0% by weight to 3% by weight, and most preferably 0% by weight to 1% by weight.
[0081] As a method for obtaining an acrylic polymer, various polymerization methods known as a synthesis method for an acrylic polymer, such as a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, a suspension polymerization method, etc., can be appropriately adopted. Among these polymerization methods, a solution polymerization method can be preferably used. As a monomer supply method when performing solution polymerization, a lump-sum charging method in which the entire amount of the monomer component is supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, etc., and is preferably 20°C or higher, more preferably 30°C or higher, even more preferably 40°C or higher, preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 140°C or lower. As a method for obtaining an acrylic polymer, photopolymerization (typically performed in the presence of a photopolymerization initiator) performed by irradiating light such as UV rays, or radiation polymerization performed by irradiating radiation such as β rays or γ rays, etc., may be adopted.
[0082] The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from any suitable organic solvent, for example, aromatic compounds (typically aromatic hydrocarbons) such as toluene, acetate esters such as ethyl acetate, aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane, etc.
[0083] The initiator (polymerization initiator) used in the polymerization can be appropriately selected from any suitable polymerization initiator depending on the type of polymerization method. The polymerization initiator may be one type only, or two or more types may be used.
[0084] Examples of the polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, and the like. azo initiators such as 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl)peroxydicarbonate, di( peroxide-based initiators such as 4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butyl peroxydicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; redox-based initiators combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate; substituted ethane-based initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds.
[0085] The amount of the polymerization initiator used may be any appropriate amount within the range that does not impair the effects of the present invention. The amount used is preferably 0.005 to 1 part by weight, more preferably 0.01 to 1 part by weight, based on 100 parts by weight of the monomer component (M).
[0086] The polymerization may contain any suitable other additives as long as they do not impair the effects of the present invention.
[0087] ≪2-2. Acrylic oligomer≫ The acrylic oligomer may be of only one type, or of two or more types.
[0088] The weight average molecular weight Mw of the acrylic oligomer is preferably 1000 to 30000, more preferably 1500 to 10000, further preferably 2000 to 8000, and particularly preferably 2000 to 5000. By using an acrylic oligomer having such a weight average molecular weight Mw, the adhesive properties and bending properties of the acrylic pressure-sensitive adhesive can be improved.
[0089] The glass transition temperature Tg of the acrylic oligomer is preferably 20° C. or higher, more preferably 30° C. or higher, even more preferably 40° C. or higher, particularly preferably 50° C. or higher, and most preferably 60° C. or higher. The upper limit of the glass transition temperature Tg of the acrylic oligomer is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 160° C. or lower.
[0090] The glass transition temperature Tg of an acrylic oligomer is a value calculated from the Fox formula based on the Tg of the homopolymer of each constituent monomer and the weight fraction (copolymerization ratio by weight) of the monomer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi)
[0091] In the above Fox formula, Tg is the glass transition temperature (unit: K) of the copolymer, Wi is the weight fraction (copolymerization ratio by weight) of monomer i in the copolymer, and Tgi is the glass transition temperature (unit: K) of the homopolymer of monomer i. As the Tg of the homopolymer, a value described in a publicly known document can be adopted, for example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. When multiple values are described in the "Polymer Handbook", the conventional value is adopted. For monomers not described in the "Polymer Handbook", the catalog value of the monomer manufacturer is adopted. As the Tg of the homopolymer of a monomer not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.
[0092] The acrylic oligomer contains an alicyclic alkyl (meth)acrylate as a main constituent monomer component. The alicyclic alkyl (meth)acrylate may be of one type only or of two or more types.
[0093] Examples of alicyclic alkyl (meth)acrylates include cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylic acid esters having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0094] As the alicyclic alkyl (meth)acrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred, in that they can further exert the effects of the present invention.
[0095] The content ratio of the alicyclic alkyl (meth)acrylate relative to the total amount of the constituent monomer components of the acrylic oligomer is preferably 10% by weight to 99% by weight, more preferably 30% by weight to 99% by weight, even more preferably 50% by weight to 98% by weight, particularly preferably 70% by weight to 98% by weight, and most preferably 90% by weight to 98% by weight, in order to further exhibit the effects of the present invention.
[0096] The acrylic oligomer is preferably a carboxyl group-containing acrylic oligomer, since it can more effectively exert the effects of the present invention.
[0097] The carboxyl group-containing acrylic oligomer preferably contains (meth)acrylic acid as a constituent monomer component. As the (meth)acrylic acid, acrylic acid is preferred in that the effects of the present invention can be more effectively exhibited.
[0098] The content of (meth)acrylic acid relative to the total amount of constituent monomer components of the acrylic oligomer is preferably 0.1% by weight to 20% by weight, more preferably 1% by weight to 10% by weight, even more preferably 2% by weight to 8% by weight, and particularly preferably 3% by weight to 7% by weight, in order to further exert the effects of the present invention.
[0099] The acrylic oligomer may contain a chain alkyl (meth)acrylate having a chain alkyl group as a constituent monomer component, and the chain alkyl (meth)acrylate having a chain alkyl group may be one type or two or more types. Here, the chain alkyl group includes linear and branched.
[0100] The chain alkyl (meth)acrylate is preferably a chain alkyl (meth)acrylate having a chain alkyl group having 1 to 20 carbon atoms, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and the like. acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0101] As the chain alkyl (meth)acrylate, methyl methacrylate is preferred in that the effects of the present invention can be more effectively exhibited.
[0102] The content ratio of the chain alkyl (meth)acrylate to the total amount of the constituent monomer components of the acrylic oligomer is preferably 70% by weight or less, more preferably 50% by weight or less, even more preferably 30% by weight or less, particularly preferably 10% by weight or less, and most preferably 5% by weight or less.
[0103] The acrylic oligomer can be obtained by polymerizing the constituent monomer components by various polymerization methods. When polymerizing to obtain the acrylic oligomer, any suitable additive may be used within a range that does not impair the effects of the present invention. Examples of such additives include a polymerization initiator and a chain transfer agent.
[0104] <2-3. Crosslinking Agent> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains two or more types of crosslinking agents as the crosslinking agent, as described above. That is, the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains two or more types of crosslinking agents in combination as the crosslinking agent. If the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains only one type of crosslinking agent, the effects of the present invention may not be achieved.
[0105] As described above, the crosslinking agents contained in the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention are two or more types, preferably two to five types, more preferably two to four types, even more preferably two to three types, and particularly preferably two types.
[0106] As the two or more types of crosslinking agents contained in the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention, any appropriate crosslinking agent may be used as long as the effects of the present invention are not impaired. Examples of such crosslinking agents include at least two types of crosslinking agents selected from the group consisting of epoxy crosslinking agents, isocyanate crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, and peroxides.
[0107] The two or more crosslinking agents contained in the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention preferably contain an epoxy crosslinking agent, and more preferably contain two types of an epoxy crosslinking agent and an isocyanate crosslinking agent, in order to further exert the effects of the present invention. The epoxy crosslinking agent may be only one type, or may be two or more types. The isocyanate crosslinking agent may be only one type, or may be two or more types.
[0108] When the crosslinking agent contains an epoxy-based crosslinking agent, the content of the epoxy-based crosslinking agent relative to 100 parts by weight of the acrylic polymer is preferably 0.05 parts by weight or more, more preferably 0.05 parts by weight or more and less than 2 parts by weight, even more preferably 0.1 parts by weight or more and less than 1.5 parts by weight, even more preferably 0.2 parts by weight or more and less than 1.0 parts by weight, particularly preferably 0.3 parts by weight or more and less than 1.0 parts by weight, and most preferably 0.4 parts by weight or more and less than 1.0 parts by weight. If the content of the epoxy-based crosslinking agent is within the above range, the effect of the present invention can be more effectively expressed. If the content of the epoxy-based crosslinking agent is too small, the effect of the present invention may not be expressed, for example, the adhesion between the acrylic pressure-sensitive adhesive and the adherend may be reduced. If the content of the epoxy-based crosslinking agent is too large, the effect of the present invention may not be expressed, for example, the adhesion between the acrylic pressure-sensitive adhesive and the adherend may be reduced.
[0109] When the crosslinking agent contains an epoxy crosslinking agent and an isocyanate crosslinking agent, the content of the isocyanate crosslinking agent relative to 100 parts by weight of the acrylic polymer is preferably 0.06 parts by weight or more, more preferably 0.06 parts by weight or more and less than 0.20 parts by weight, even more preferably 0.07 parts by weight or more and less than 0.18 parts by weight, particularly preferably 0.07 parts by weight or more and less than 0.16 parts by weight, and most preferably 0.08 parts by weight or more and less than 0.15 parts by weight. If the content of the isocyanate crosslinking agent is within the above range, the effect of the present invention can be more effectively exhibited. If the content of the isocyanate crosslinking agent is too small, the effect of the present invention may not be exhibited, for example, the cohesive force of the acrylic adhesive may be reduced. If the content of the isocyanate crosslinking agent is too large, the effect of the present invention may not be exhibited, for example, the adhesion between the acrylic adhesive and the adherend may be reduced.
[0110] The crosslinking agent may be contained in the acrylic pressure-sensitive adhesive in a form after crosslinking reaction, a form before crosslinking reaction, a form after partial crosslinking reaction, an intermediate or composite form thereof, etc. The crosslinking agent is typically contained in the acrylic pressure-sensitive adhesive in a form after crosslinking reaction.
[0111] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, and the like. Examples of epoxy crosslinking agents include glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of commercially available epoxy crosslinking agents include "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Company, Inc.
[0112] The isocyanate crosslinking agent may be a compound having two or more isocyanate groups (including isocyanate regenerating polar groups in which the isocyanate group is temporarily protected by a blocking agent or oligomerization) in one molecule. Examples of the isocyanate crosslinking agent include aromatic isocyanates such as tolylene diisocyanate and xylylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.
[0113] Examples of the isocyanate-based crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate; trimethylolpropane / tolylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate HL), and isocyanurate of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, isocyanate adducts such as CORONATE HX; trimethylolpropane adduct of xylylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D110N), trimethylolpropane adduct of xylylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D120N), trimethylolpropane adduct of isophorone diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D140N), trimethylolpropane adduct of hexamethylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D160N); polyether polyisocyanate, polyester polyisocyanate, and adducts of these with various polyols; and polyisocyanates multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among these, aromatic isocyanates and alicyclic isocyanates are preferred because they can achieve a good balance between deformability and cohesive strength.
[0114] 2-4. Other ingredients The acrylic adhesive composition according to the embodiment of the present invention may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of such other components include polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifier resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antiaging agents, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foil-like materials, ultraviolet absorbers, antioxidants, light stabilizers, nucleating agents, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.
[0115] 3. Flexible Devices A flexible device according to an embodiment of the present invention includes an adhesive film according to an embodiment of the present invention.
[0116] The adhesive film according to the embodiment of the present invention can exhibit high flexibility, sufficient adhesion to the adherend, and high cohesive strength of the acrylic adhesive, and therefore can be suitably used in flexible devices such as bendable devices (devices that can be bent) having movable bending parts, foldable devices (devices that can be folded), and rollable devices (devices that can be rolled up).
[0117] The flexible device of the present invention may include any other appropriate member as long as it includes the adhesive film according to the embodiment of the present invention.
[0118] FIG. 1 is a schematic cross-sectional view showing one embodiment of a flexible device of the present invention as a representative example of one use form of an adhesive film according to an embodiment of the present invention. In FIG. 1, a flexible device 1000 according to an embodiment of the present invention includes a cover film 10, an adhesive layer 20, a polarizing plate 30, an adhesive layer 40, a touch sensor 50, an adhesive layer 60, an OLED 70, and an adhesive film 100 according to an embodiment of the present invention. In FIG. 1, the adhesive film 100 according to an embodiment of the present invention is composed of an adhesive layer 80 and a base layer 90. The adhesive layer 20, the adhesive layer 40, and the adhesive layer 60 may be an adhesive layer containing an adhesive having the same composition as the adhesive layer 80 constituting the adhesive film 100 according to an embodiment of the present invention, or may be an adhesive layer containing an adhesive having a different composition. EXAMPLES
[0119] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited thereto. In the following description, "parts" and "%" are by weight unless otherwise specified.
[0120] The abbreviations and details of raw materials used in the following Production Examples, Examples, and Comparative Examples are as follows: 2EHA: 2-ethylhexyl acrylate LA: Lauryl acrylate BA: n-butyl acrylate 4HBA: 4-hydroxybutyl acrylate NVP: N-vinyl-2-pyrrolidone AIBN: 2,2'-azobisisobutyronitrile CHMA: Cyclohexyl methacrylate AA: Acrylic acid C / HX: Coronate HX (Tosoh Corporation, isocyanate-based crosslinking agent) TETRAD-C (Mitsubishi Gas Chemical Company, epoxy crosslinking agent) Nasem ferric: Iron catalyst (manufactured by Nippon Kagaku Sangyo Co., Ltd.)
[0121] <Adhesion to polyimide film at peel speed of 10 mm / min> The adhesive film was cut to a width of 25 mm and a length of 100 mm, the release liner was peeled off to expose the adhesive, and the adhesive was then attached to a polyimide film (product name "Upilex 50S", manufactured by Ube Industries) using a 2 kg hand roller back and forth once to obtain a sample for evaluation. The obtained evaluation sample was stored at room temperature for 30 minutes, and then measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. After setting the evaluation sample on the tensile tester, the tensile test was started. The conditions of the tensile test were peel angle: 180 degrees, peel speed (pulling speed): 10 mm / min. The load when peeling the adhesive film from the polyimide film (Upilex 50S) was measured, and the average load at that time was taken as the adhesive strength.
[0122] <Adhesion to polyimide film at peel speed of 6000mm / min> The adhesive film was cut to a width of 25 mm and a length of 100 mm, the release liner was peeled off to expose the adhesive, and the adhesive was then attached to a polyimide film (product name "Upilex 50S", manufactured by Ube Industries) using a 2 kg hand roller back and forth once to obtain a sample for evaluation. The obtained evaluation sample was stored at room temperature for 30 minutes, and then measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. After setting the evaluation sample on the tensile tester, the tensile test was started. The conditions of the tensile test were peel angle: 180 degrees, peel speed (pulling speed): 6000mm / min. The load when peeling the adhesive film from the polyimide film (Upilex 50S) was measured, and the average load at that time was taken as the adhesive strength.
[0123] <Preparation of test specimens for measuring storage modulus at -20℃ and creep value at -20℃> The coating solution of the acrylic adhesive composition was applied to a release sheet (manufactured by Mitsubishi Chemical Corporation, MRV50T100J) made of polyester resin with a thickness of 50 μm and one side of which was silicone-treated, so that the thickness after drying was 15 μm, and dried under conditions of a drying temperature of 135° C. and a drying time of 1 minute. Next, the surface of the obtained adhesive layer was bonded to the silicone-treated surface of a release sheet (manufactured by Mitsubishi Chemical Corporation, MRQ50T100J) made of polyester resin with a thickness of 50 μm and one side of which was silicone-treated, so as to be in contact with the surface, to obtain an adhesive film. This was aged at 50° C. for 1 day to obtain a test piece.
[0124] <Storage modulus at -20℃> Only the adhesive layer was taken out from the test piece, laminated to a thickness of about 1 mm, and this was punched out to a diameter of 8 mm to prepare a cylindrical pellet, which was used as a measurement sample. The obtained measurement sample was fixed to a jig of φ8 mm parallel plates using a dynamic viscoelasticity measuring device (manufactured by TA Instruments, DHR-2), and the storage modulus was calculated. The measurement conditions were as follows: Measurement: Shear mode Temperature range: -50℃~200℃ Heating rate: 5℃ / min Frequency: 1Hz Distortion: 0.1%
[0125] <Creep value at -20℃> Only the adhesive layer was taken out from the test piece, laminated to a thickness of about 1 mm, and this was punched out to a diameter of 8 mm to prepare a cylindrical pellet, which was used as a measurement sample. Using a dynamic viscoelasticity measuring device (TA Instruments, DHR-2), the obtained measurement sample was fixed to a jig with a φ8 mm parallel plate. The deformation strain (%) after applying a deformation stress of 10 kPa at -20°C and holding for 600 seconds was taken as the creep value at -20°C.
[0126] <Shear retention rate> A polyimide film (trade name "Upilex 50S", manufactured by Ube Industries) was attached to an acrylic plate using double-sided tape (manufactured by Nitto Denko Corporation, No. 500). The adhesive film was cut to a width of 25 mm and a length of 100 mm, and the release liner was peeled off to expose the adhesive. The adhesive was then attached to the surface of the polyimide film attached to the acrylic plate with a hand roller so that the adhesive surface was 25 mm x 25 mm in size, to obtain a sample for evaluation. The obtained evaluation sample was autoclaved under conditions of 50°C, 0.5 MPa, and 15 minutes, and then measured with a tensile tester. Shimadzu Corporation's Autograph AG-Xplus 5kN was used as the tensile tester. After setting the evaluation sample in the tensile tester, it was pulled 0.5 mm in the shear direction at a speed of 10 mm / min and held for 30 minutes. The maximum test force (F0) and the test force after 30 minutes (F1) were recorded, and the shear retention rate was calculated using Equation 1. (Formula 1)F1×100 / F0
[0127] <Weight average molecular weight Mw> The weight average molecular weight was measured by gel permeation chromatography (GPC). Specifically, an Agilent 1260 Infinity (manufactured by Agilent Technologies, Inc.) was used as a GPC measuring device, and a tetrahydrofuran solution containing 0.1% by weight of an amine-based component was prepared in consideration of the polymer concentration of the sample, left for 20 hours, filtered through a 0.45 μm membrane filter, and the obtained filtrate was subjected to GPC measurement. Measurements were performed under the following conditions, and values were calculated in terms of standard polystyrene. (Molecular weight measurement conditions) Sample concentration: 0.1% by weight (amine-based component added tetrahydrofuran solution) Sample injection volume: 100μL Column: Product name "TSKgel GMH-H(S)" (manufactured by Tosoh Corporation) Eluent: Tetrahydrofuran with added amine components ·Flow rate: 0.5mL / min Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40℃ Standard sample: Polystyrene (PS)
[0128] [Production Example 1]: Production of acrylic polymer A four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser was charged with 70 parts by weight of 2EHA, 8 parts by weight of LA, 20 parts by weight of BA, 1 part by weight of 4HBA, 0.6 parts by weight of NVP, and 0.1 parts by weight of AIBN as a polymerization initiator, and ethyl acetate was added so that the total concentration of these was 47% by weight. The system was replaced with nitrogen over one hour with gentle stirring, and the liquid temperature in the flask was kept at around 56°C to carry out a polymerization reaction for 6 hours. After completion of the reaction, ethyl acetate was added to adjust the polymer concentration to 24% by weight, and an acrylic polymer solution was obtained.
[0129] [Production Example 2]: Production of acrylic oligomer CHMA: 95 parts by weight and AA: 5 parts by weight as monomer components, α-methylstyrene dimer (manufactured by Nippon Oil & Fats Corporation, trade name "Nofumer MSD"): 10 parts by weight as a chain transfer agent, and AIBN: 10 parts by weight as a thermal polymerization initiator were added, and toluene was mixed so that the raw material concentration was 50% by weight, and the mixture was reacted at 85°C for 2 hours under a nitrogen atmosphere. The temperature was then raised to 86°C and the mixture was reacted for 1.5 hours to obtain an acrylic oligomer. The weight average molecular weight Mw of the acrylic oligomer was 4000, and the glass transition temperature (Tg) was 67°C.
[0130] Example 1 Acrylic polymer: 100 parts by weight, acrylic oligomer: 10 parts by weight, C / HX: 0.1 parts by weight as an isocyanate crosslinking agent, TETRAD-C: 0.5 parts by weight as an epoxy crosslinking agent, and ferric nasem: 0.01 parts by weight as a catalyst were mixed, thoroughly stirred, and diluted with ethyl acetate and acetylacetone of 1% by weight of the solvent content so that the total solid content was 17% by weight, to obtain a coating solution of acrylic adhesive composition (1). The obtained coating solution of acrylic adhesive composition (1) was applied to a polyester film (manufactured by Toray Industries, Inc., S-10#50) so that the thickness after drying was 15 μm, and dried under conditions of a drying temperature of 135° C. and a drying time of 1 minute. Next, the silicone-treated surface of a release sheet (manufactured by Mitsubishi Chemical Corporation, product name: MRQ50T100J) made of polyester resin with a thickness of 50 μm and one side of which was silicone-treated was attached to the surface of the obtained adhesive layer so that it was in contact with the silicone-treated surface, to obtain an adhesive film (1). This was aged at 50° C. for one day and then various evaluations were carried out. The results are shown in Table 1.
[0131] [Examples 2 to 6] Except for changing the raw material composition as shown in Table 1, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic pressure-sensitive adhesive compositions (2) to (6) and pressure-sensitive adhesive films (2) to (6). These were aged at 50°C for 1 day and various evaluations were carried out. The results are shown in Table 1.
[0132] [Comparative Examples 1 to 4] Except for changing the raw material composition as shown in Table 1, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic pressure-sensitive adhesive compositions (C1) to (C4) and pressure-sensitive adhesive films (C1) to (C4). These were aged at 50°C for 1 day and various evaluations were carried out. The results are shown in Table 1.
[0133] [Table 1] [Industrial Applicability]
[0134] The pressure-sensitive adhesive film and acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention can be used for so-called flexible devices such as foldable devices and rollable devices. [Explanation of symbols]
[0135] 1000 Flexible Devices 100 Adhesive Film 10 Cover film 20 Adhesive layer 30 Polarizing plate 40 Adhesive layer 50 Touch Sensor 60 Adhesive layer 70 OLED 80 Adhesive layer 90 Base material layer
Claims
1. An adhesive film including an adhesive layer made of an acrylic adhesive, The adhesive strength of the acrylic pressure-sensitive adhesive to a polyimide film is 700 gf / 25 mm or more at 23° C., a peel speed of 10 mm / min, and a peel angle of 180 degrees. the adhesive strength of the acrylic pressure-sensitive adhesive to a polyimide film is 1300 gf / 25 mm or more at 23° C., a peel speed of 6000 mm / min, and a peel angle of 180 degrees; The storage modulus of the acrylic pressure-sensitive adhesive at -20°C is less than 140 kPa. Adhesive film.
2. The pressure-sensitive adhesive film according to claim 1 , wherein the acrylic pressure-sensitive adhesive has a shear retention of 50% or more.
3. The pressure-sensitive adhesive film according to claim 1, wherein the acrylic pressure-sensitive adhesive has a creep value of 45% or more at -20°C.
4. An acrylic pressure-sensitive adhesive composition for forming an acrylic pressure-sensitive adhesive, The acrylic pressure-sensitive adhesive composition comprises an acrylic polymer, an acrylic oligomer, and two or more types of crosslinking agents. An acrylic pressure-sensitive adhesive composition.
5. The acrylic pressure-sensitive adhesive composition according to claim 4 , wherein the two or more types of crosslinking agents include an epoxy crosslinking agent.
6. The acrylic pressure-sensitive adhesive composition according to claim 5 , wherein the two or more types of crosslinking agents include an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent.
7. The acrylic pressure-sensitive adhesive composition according to claim 5 , wherein the content of the epoxy crosslinking agent relative to 100 parts by weight of the acrylic polymer is 0.05 parts by weight or more.
8. The acrylic pressure-sensitive adhesive composition according to claim 4 , wherein the content of the acrylic oligomer is 5 parts by weight or more based on 100 parts by weight of the acrylic polymer.
9. The acrylic pressure-sensitive adhesive composition according to claim 4 , wherein the acrylic oligomer is a carboxyl group-containing acrylic oligomer.
10. The acrylic pressure-sensitive adhesive composition according to claim 4 , wherein the acrylic polymer is a hydroxyl group-containing acrylic polymer.
11. A flexible device comprising the adhesive film according to any one of claims 1 to 3.
Citation Information
Patent Citations
Optical recording and reproducing unit
JP1981000039A
Alkailine zinc storage battery
JP1988076271A